The use of lateral wedge insoles delays osteoarthritis progression and improves clinical outcomes in medial meniscus posterior root repair - Koki Kawada; Yusuke Yokoyama; Yuki Okazaki; Masanori Tamura; Toshifumi Ozaki; Takayuki Furumatsu (Journal of Experimental Orthopaedics)
Abstract Purpose The purpose of this retrospective study was to evaluate the efficacy of using a lateral wedge insole (LWI) during the first 3 months after medial meniscus posterior root (MMPR) repair. Methods Overall, 179 patients were categorized into LWI use (LWI group, 90 patients) and nonuse (control group, 89 patients) groups. Patients in the LWI group were instructed to wear an LWI from the initiation of load bearing up to 3 months postoperatively. Medial meniscus extrusion (MME) was evaluated preoperatively and 1 year postoperatively, Kellgren–Lawrence (KL) grade and clinical scores were evaluated preoperatively and 2 years postoperatively, and second‐look arthroscopic meniscal healing scores were evaluated at 1 year postoperatively. Results The proportion of patients with KL grade progression at 2 years postoperatively was significantly lower in the LWI group than in the control group (23.3% vs. 39.3%; p = 0.024). Change in the MME at 1 year postoperatively was significantly smaller in the LWI group than in the control group (1.1 ± 1.2 vs. 1.6 ± 1.4 mm; p = 0.042). The Lysholm score (p = 0.003) and Knee Injury and Osteoarthritis Outcome Scores‐sport and recreation function (p = 0.027) at 2 years postoperatively were significantly superior in the LWI group than in the control group. The arthroscopic meniscal healing score after 1 year was not significantly different between the LWI and control groups (total score, 7.6 ± 1.1 vs. 7.4 ± 1.3 points; p = 0.732). The anteroposterior width of the repaired posterior root at 1 year second‐look evaluation was significantly broader in the LWI group than in the control group (7.7 ± 1.6 vs. 6.9 ± 1.6 mm; p = 0.001). Conclusions The use of LWI is an effective way to delay postoperative osteoarthritis progression and improve clinical outcomes after MMPR repair. Level of Evidence Level III.